SARS-CoV-2 infection in travelers from abroad upon their arrival at Santiago de Cuba - Luis Eugenio Valdés García; Yusmel Jaqueman Dussac; Yaimara Gutierrez de la Cruz; Ariadna Domínguez Mateos (Centro Provincial de Información de Ciencias Médicas, 2024)
Introduction: The study of travelers is important and has been a variable significantly associated with the number of covid-19 cases.   Objective: To characterize the travelers infected with SARS-CoV-2 according to epidemiologic and sociodemographic variables of interest.   Methods: An ecological study of temporary series was carried out, of travelers from abroad, residents in Santiago de Cuba or whose final destination was this province, that arrived at the country between March 11, 2020 and November 11, 2022. The sources of information were the travelers' records established by the Provincial Center of Hygiene, Epidemiology and Microbiology of this province and the results of polymerase chain reaction tests of the Provincial Laboratory of Microbiology.   Results: Sixty-four thousand nine-hundred eighty four travelers were received, of which 568 were positive, with prevalence of the asymptomatic and the diagnosis at the fifth day of arrival.    Conclusions: The control on the travelers influenced in the pattern of transmission of the disease; as long as, the realization of a second test at the fifth day allowed to find a high percentage of positivity. Some characteristics of morbidity in this group of cases differed from the incidence in the general population, such as the clinical forms, age and space distribution.